IMPACTO DO GRAU DA INOVAÇÃO TECNOLÓGICA NA RELAÇÃO ENTRE A INTEGRAÇÃO DA CADEIA DE SUPRIMENTOS E O DESEMPENHO DO PROCESSO OPERACIONAL - Oliveira, Rinaldo de Castro (2020)
The various types of innovation, with different effects on the supply chain and organizational performance, considering operational processes, have been a relevant topic in the literature, due to technological innovations generate consequences for supplie